Microsoft Outlook 2007 programming : jumpstart for power users and administrators - Mosher, Sue, 1953- (Digital Press, 2007)
Microsoft Outlook is the most widely used e-mail program and offers the most programmability. Sue Mosher introduces key concepts for programming Outlook using Visual Basic for Applications, custom Outlook forms, and external scripts, without the need for additional development tools. For those who manage Outlook installations, it demonstrates how to use new features in the Outlook 2007 programming model such as building scripts that can create rules and views and manage categories. Power users will discover how to enhance Outlook with custom features, such as the ability to process incoming mail and extract key information. Aimed at the non-professional programmer, it also provides a quick guide to Outlook programming basics for pro developers who want to dive into Outlook integration. - Publisher.